Linking environmental stress, feeding‐shifts and the 'island syndrome': a nutritional challenge hypothesis. Issue 1 (16th October 2013) - Blanco, Guillermo; Laiolo, Paola; Fargallo, Juan A.
Abstract: Adaptation to insular environments often arises from changes and innovations in feeding behaviour allowing expanded foraging habits and an increased niche breadth. These shifts and innovations have traditionally been thought to be related to community‐wide processes, but could also be the direct result of environmental constraints determining the abundance, availability and suitability of a particular food providing specific nutrients for survival, growth and reproduction. The link between environmental constraints on nutrients and life‐history of insular organisms can help in understanding the convergent set of adaptations sustaining the 'island syndrome'. We tested whether a potential insular nutrient shortage can drive diet shifts, nutritional biochemistry and growth stress, thus contributing to the modulation of life‐history traits in a large passerine bird, the red‐billed chough ( Pyrrhocorax pyrrhocorax ). Results supported the insular nutritional challenge hypothesis, linked to an insular insect shortage. An insect shortage may in turn have determined the reduced consumption of this source of protein but increased consumption of other arthropods, and notably fruits, by insular nestlings and fully‐grown individuals. Island birds showed comparatively low circulating levels of nutrients and metabolites associated with the consumption of protein‐rich animal matter as opposed to carbohydrate‐rich vegetal matter, as well as high growth stress reflected in poor feather quality. We propose that feeding shifts derived from an insular insect shortage may exert a strong influence on the allocation of limited time, energy and nutrients among competing functions associated with physiological changes and investment in reproduction and self‐maintenance. Traits and patterns generally defining the insular syndrome could thus be linked to particular insular nutrient constraints forcing feeding shifts and nutritional challenges with physiological, demographic and life‐history consequences.